2021
DOI: 10.1155/2021/8817725
|View full text |Cite
|
Sign up to set email alerts
|

The Hydration and Compressive Strength of Cement Mortar Prepared by Calcium Acetate Solution

Abstract: Calcium acetate is the major component of the waste solution produced in treating recycled concrete aggregate (RCA) with acetic acid. Thus, the current work aims to explore the influence of calcium acetate solution on the performance of ordinary Portland cement. For this purpose, cement pastes and mortars were prepared using different concentrations, namely, 1, 2, and 3%, of calcium acetate solution. The heat evolution results confirmed that the calcium acetate solution at a concentration of 2% could accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In spite of using mineral admixture to increase the durability characteristics of building materials bonded by cement [20], CaA has been mentioned in literature as an accelerator and water reducer in silica fume blended cement [21], but research on its use as a modifier for concrete properties is very rare. One study mentioned the use of calcium acetate as a waste solutions from the treatment of recycled concrete aggregate with acetic acid as an admixture [22]. In summary, the results of the current work confirmed that the concrete composites incorporated with CaA had more compressive strength (more than 28% increase) and less water absorption (more than 83% decrease) owing to the more dense and compacted texture compared to plain concrete.…”
Section: Resultssupporting
confidence: 76%
“…In spite of using mineral admixture to increase the durability characteristics of building materials bonded by cement [20], CaA has been mentioned in literature as an accelerator and water reducer in silica fume blended cement [21], but research on its use as a modifier for concrete properties is very rare. One study mentioned the use of calcium acetate as a waste solutions from the treatment of recycled concrete aggregate with acetic acid as an admixture [22]. In summary, the results of the current work confirmed that the concrete composites incorporated with CaA had more compressive strength (more than 28% increase) and less water absorption (more than 83% decrease) owing to the more dense and compacted texture compared to plain concrete.…”
Section: Resultssupporting
confidence: 76%
“…More recently, CA has been used to alleviate yield loss in rice [36] and determine the potential acidity of tropical soils [37]. For other applications, CA has been used as starting reagent to return to common compounds such as nano CaO [38] and CaCO 3 [39] and prepare other compounds such as calcium phosphates [40], acetone [41], composite ceramic compounds [42], anhydrite calcium sulfate nanowhiskers [43], and cement mortar [44].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the values of UCS for the D-3 sample (30% CP) and group E samples (40% CP) show a slight increase. Previous investigations have shown that the strength of the CGFB samples is mainly determined by the cement hydration [30][31][32][33][34]. Generally, the stronger the cement hydration is, the larger the corresponding strength of the CGFB sample is.…”
Section: Uniaxial Compression Test Resultsmentioning
confidence: 99%